2019
DOI: 10.1371/journal.pone.0208464
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of quality of life measures in patients with endometriosis

Abstract: ObjectivesEndometriosis and quality of life has been the subject of much research, however, there is little consensus on how best to evaluate quality of life in endometriosis, resulting in many and diverse scales being used. In our study, we aim to identify quality of life scales used in endometriosis, to review their strengths and weaknesses and to establish what would define an ideal scale in the evaluation of endometriosis-related quality of life.Materials and methodsA search of the MEDLINE and EMBASE datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 208 publications
(167 reference statements)
2
89
0
3
Order By: Relevance
“…If HCPs take the patient’s pain seriously, the pain becomes legitimate and it is easier for the patient to understand and manage. A review highlighted that it is essential for HCPs to evaluate HRQoL in persons with endometriosis 53. Listening to the patient enables the development of a partnership which helps them to manage and regain control over pain, and is crucial in empowering them to take an active part in decisions about their own care planning 54.…”
Section: Discussionmentioning
confidence: 99%
“…If HCPs take the patient’s pain seriously, the pain becomes legitimate and it is easier for the patient to understand and manage. A review highlighted that it is essential for HCPs to evaluate HRQoL in persons with endometriosis 53. Listening to the patient enables the development of a partnership which helps them to manage and regain control over pain, and is crucial in empowering them to take an active part in decisions about their own care planning 54.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the core symptoms of endometriosis from the patient-perspective could facilitate earlier diagnosis of endometriosis, however there are currently no validated measures routinely used by healthcare professionals for this purpose [59]. Similarly, the ESD and EIS may have use for monitoring response to treatment in clinical practice and providing additional insights into the burden of disease beyond generic HRQoL (e.g., and legacy PRO measures (e.g., EHP-30) commonly used for this purpose [60].…”
Section: Discussionmentioning
confidence: 99%
“…We assessed pain scores in 54 women undergoing diagnostic laparoscopy for suspected endometriosis. Pelvic pain symptoms were recorded using the pain dimension of the EHP-30 questionnaire, an extensively validated endometriosis-specific health-related quality of life measurement (25,26). We found that pain scores in women with endometriosis (mean and SEM, 45.5±5.54) were comparable to previous reports using the EHP-30 questionnaire in large cohorts of women from the UK (mean pain score 43.3, n=594 women), USA (mean pain score 49.3, n=225 women) and Australia (mean pain score 40.7, n=189 women) (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%